Safety and clinical outcomes of endovascular therapy versus medical management in late presentation of large ischemic stroke - Mujanović, Adnan; Strbian, Daniel; Demeestere, Jelle; Marto, João Pedro; Puetz, Volker; Nogueira, Raul G; Abdalkader, Mohamad; Nagel, Simon; Raymond, Jean; Ribo, Marc; Michel, Patrik; Yoshimura, Shinichi; et al. (European stroke journal, 2024)
Introduction: The benefit of endovascular therapy (EVT) among stroke patients with large ischemic core (ASPECTS 0-5) in the extended time window outside of trial settings remains unclear. We analyzed the effect of EVT among these stroke patients in real-world settings. - Patients and methods: The CT for Late Endovascular Reperfusion (CLEAR) study recruited patients from 66 centers in 10 countries between 01/2014 and 05/2022. The extended time-window was defined as 6-24 h from last-seen-well to treatment. The primary outcome was shift of the 3-month modified Rankin scale (mRS) score. Safety outcomes included symptomatic intracranial hemorrhage (sICH) and mortality. Outcomes were analyzed with ordinal and logistic regressions. - Results: Among 5098 screened patients, 2451 were included in the analysis (median age 73, 55% women). Of patients with ASPECTS 0-5 (n = 310), receiving EVT (n = 209/310) was associated with lower 3-month mRS when compared to medical management (median 4 IQR 3-6 vs 6 IQR 4-6; aOR 0.4, 95% CI 0.2-0.7). Patients undergoing EVT had higher sICH (11.2% vs 4.0%; aOR 4.1, 95% CI 1.2-18.8) and lower mortality (31.6% vs 58.4%, aOR 0.4; 95% CI 0.2-0.9) compared to medically managed patients. The relative benefit of EVT was comparable between patients with ASPECTS 0 and 5 and 6-10 in the extended time window (interaction aOR 0.9; 95% CI 0.5-1.7). - Conclusion: In the extended time window, patients with ASPECTS 0-5 may have preserved relative treatment benefit of EVT compared to patients with ASPECTS 6-10. These findings are in line with recent trials showing benefit of EVT among real-world patients with large ischemic core in the extended time window. - Trial registration number: clinicaltrials.gov; Unique identifier: NCT04096248
Gesehen am 02.12.2024